Age and Gender Distribution of Benign Breast Lesions of Women at Port City of Bangladesh - Nahar, Nazmun; Iqbal, Mohammed; Rahman, Kazi Md Shahidur; Razzaque, Sabrina; Yeasmin, Farida; Alam, Urmee; Uddin, Md Abbas (Journal of Science Foundation, 2018)
Background: Benign breast diseases are the most common cause of breast problems. The most common symptoms are breast pain, lumpiness or a lump and nipple discharge. Triple assessment that includes clinical examination, imaging like ultrasonography (USG) or mammography and a pathological examination – FNAC or core needle biopsy has a very high accuracy rate in diagnosing, discrete benign breast diseases and this can be used for reassurance. Objective: The purpose of the present study was to determine the frequency of different types of benign neoplasm of breast lump in different age and sex. Methodology: The present study was carried out at the Department of Pathology, Chittagong Medical College, Bangladesh one year period from May 2005 to June 2006. This study was cross sectional which included 48 cases of breast neoplasm. The specimens were received from indoor patient Department of Surgery, Chittagong Medical College, Bangladesh. Histopathological examination was done. Results: This study shows the mean age of the patients was 32.91 years with age range 11 to 70 years. Most of the patients were in 31 to 50 years (45.8%) age group and female predominance than male. Fibroadenoma accounted for 76.2%. Sclerosing adenosine the second most common benign breast disease in this study accounted for 9.5% of cases. Conclusion: This study showed that among the benign breast diseases in females there were preponderance of fibroadenoma followed by sclerosing adenosine Journal of Science Foundation 2018;16(1):27-31